The Effect of Islamic Bank Financing on the Human Development Index: A Case Study of 15 Cities on Java Island - Hanifa Salsabila; Riswanti Budi Sekaringsih (Bulletin of Islamic Economics, 2022)
The Human Development Index (IPM) measures how people can access development results in obtaining income, health, and education. This study aimed to determine whether Islamic bank financing, poverty, and Gross Regional Domestic Product (GRDP) have a relationship and influence the Human Development Index in 15 cities in Java Island for 2015-2021. The quantitative approach uses secondary data from the Financial Services Authority (OJK) for Islamic bank financing data. In contrast, Poverty and GRDP data from the Central Bureau of Statistics (BPS). The data used in this study is annual data from 2015 to 2021. The estimation method used is panel data regression with the Random Effects model. The study results that the Islamic bank financing variable has a significant positive effect on HDI. Meanwhile, the Poverty and GRDP variables significantly and negatively affect the Human Development Index. Simultaneously, the variables of Islamic bank financing, poverty, and GRDP affect the Human Development Index.